Chapter 3. Excel basics - Santos, Jorge (Septentrio Educational, 2015)
<span style="background: white; color: black; line-height: 107%; font-family: 'Verdana',sans-serif; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This introductory chapter of CONΣERV IT deals with the following preparatory skills: - How to lose the fear of using a spreadsheet? - How to do basic repetitive calculations? - How to present figures and reports in scientific style? - How to efficiently select and summarize sub-groups of data? <span style="background: white; color: black; line-height: 107%; font-family: 'Verdana',sans-serif; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="background: white; color: black; line-height: 107%; font-family: 'Verdana',sans-serif; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Excel basics